Chevy Corvette: Icon Of American Life In The Fifties - Wishnoebroto, Wishnoebroto (Bina Nusantara University, 2007)
Cars not only function simply as a mean of transportation. Like paintings, the design of a car could represent a certain cultural and social phenomenon of a country. The design of Chevrolet (Chevy) Corvette is very different compared to its competitors in the 50s. The size, engine, weight, and the materials of this car were chosen based on the assumption that speed and agility is on top of everything. It was not surprising that in the 50s, the year when the first Corvette was designed and launched, The US was involved in a cold war with the Soviets. Arm race and competition to be the first was the major issue and Corvette was the first car that suggests this spirit. This paper tries to show the distinctiveness of Corvette and how it can be used to explain the character of American people in the fifties.Â